2015
DOI: 10.1038/nm.3872
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin3 mediates somatostatin-dependent negative feedback control of insulin secretion

Abstract: The peptide hormone Urocortin3 (Ucn3) is abundantly expressed by mature beta cells, yet its physiological role is unknown. Here we demonstrate that Ucn3 is stored and co–released with insulin and potentiates glucose–stimulated somatostatin secretion via cognate receptor on delta cells. Further, we found that islets lacking endogenous Ucn3 demonstrate fewer delta cells, reduced somatostatin content, impaired somatostatin secretion and exaggerated insulin release, and that these defects are rectified by syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
217
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 71 publications
26
217
0
1
Order By: Relevance
“…Glucose (1 g/kg, ip) was administered followed by tail blood glucose measurements every 30 min for two hours. Continuous glucose monitoring was performed as previously described (20). Briefly, the sensor (Dexcom7 system, Dexcom, San Diego, CA) was inserted under the skin in anesthetized mice and calibrated twice daily based on blood glucose values determined with a LifeScan One Touch Ultra glucometer (Chesterbrook, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose (1 g/kg, ip) was administered followed by tail blood glucose measurements every 30 min for two hours. Continuous glucose monitoring was performed as previously described (20). Briefly, the sensor (Dexcom7 system, Dexcom, San Diego, CA) was inserted under the skin in anesthetized mice and calibrated twice daily based on blood glucose values determined with a LifeScan One Touch Ultra glucometer (Chesterbrook, PA).…”
Section: Methodsmentioning
confidence: 99%
“…1H,I), urocortin 3 (Ucn3) was also decreased (Table 2). A recent study demonstrated a reduction in the Sst + cell number in the pancreas of Ucn3-deficient mice (van der Meulen et al, 2015), suggesting that there is a similar relationship between Ucn3…”
Section: Characterization Of Nkx22mentioning
confidence: 97%
“…ATP-sensitive potassium (KATP) channels are key players in the regulation of insulin and somatostatin secretion from pancreatic β and δ cells, respectively, because activation of KATP channels completely abolishes glucose-induced insulin and somatostatin secretion (5,37,38 and control mice to a similar extent, thus indicating that increased somatostatin secretion was not due to changes in KATP channel activity in pancreatic δ cells ( Figure 3A). In contrast, diazoxide inhibited glucose-induced insulin secretion to the same extent in islets isolated from Sst-Cre +/-Cul4b fl/Y mice and from their WT littermates, possibly because of the common essential downstream pathway mediated by KATP channels governing insulin secretion in pancreatic β cells in mice of both genotypes ( Figure 3B).…”
Section: The Journal Of Clinical Investigation R E S E a R C H A R Tmentioning
confidence: 99%
“…L-type calcium channels are responsible for the influx of extracellular calcium during hormone secretion. We therefore measured high glucose-and high potassium-induced calcium signals in iso- In addition to intracellular calcium, the second messenger cAMP, the G q -PLC pathway, and kinase signaling are actively involved in hormone secretion from pancreatic islets (5,13,(39)(40)(41). Therefore, we preincubated the islets with several inhibitors, including cAMP-PKA signaling inhibitors Rp-CAMPs and H89, G q -PLC inhibitor U73122, MEK inhibitor U0126, and adenyl cyclase (AC) inhibitor 2′,5′-dideoxyadenosine (DDA), and we examined glucose-induced somatostatin secretion patterns ciency in the pancreatic β cells of Ins2-Cre +/-Cul4b fl/Y mice did not significantly affect insulin and somatostatin secretion levels in response to high glucose relative to trends found for Ins2-Cre +/-mice (Supplemental Figure 3, A and B).…”
mentioning
confidence: 99%